Peningkatan Motivasi Belajar Siswa Melalui Metode Pembelajaran pada Mata Pelajaran IPA Kelas III SD IT Ummi Aida Medan Tembung - Aidil Akbar Nasution; Aufa Aufa; Faradiba Mega Puan Maharani; Khairunnisa Nasution; Widiya Widiya (Departement of Mathematics Education, 2023)
The application of learning methods in science subjects can influence student learning motivation which can encourage student learning outcomes. Learning activities will be successful if students have motivation in learning. The purpose of this study was to find out and obtain information to become more familiar with and test the effect of the learning methods applied by teachers in increasing student learning motivation. The method used in this study is a qualitative method with research instruments through interviews, observation and documentation. The results of this study explain and provide an overview of increasing student motivation through learning methods in science subjects in class III SD IT Ummi Aida which are carried out effectively and can increase student motivation by the homeroom teacher. Where to use a variety of effective learning methods that are tailored to the interests of students in the delivery of science subject matter. For example, the teacher uses the demonstration method with media props, discussion and question and answer methods as a form of repetition of science subject matter. In addition, the teacher also provides a motivational direction in the form of student guidance in providing direction for the importance of preserving nature. Thus, the results of this study can be concluded that it can be done effectively and there is an increase in student motivation by using learning methods.